EFFICACY AND SAFETY OF MORPHINE HYDROCHLORIDE IN CANCER PATIENTS WITH CHRONIC PAIN - R. A. Zukov; O. P. Bobrova; G. N. Gildeeva; D. V. Butuzova; E. A. Ershova (Сибирский онкологический журнал)
Purpose of the study: to assess the efficacy and safety of morphine hydrochloride in the form of 10 mg filmcoated tablets and 1 % solution for injection in cancer patients with chronic pain syndrome of strong intensity.Material and Methods. The study included 110 cancer patients with chronic pain syndrome of strong intensity. The study was conducted in compliance with the principles of the Helsinki Declaration, ICH GCP, GOST R 52379-2005, as well as other Russian laws regulating the conduct of clinical trials and work with opioid analgesics. Patients were randomized at a 1:1 ratio. Group I received 10 mg film-coated morphine tablets, 1 tablet orally every 4 hours for 7 days. Group II received 1 % morphine solution for injection, intramuscularly, 4 mg every 4 hours for 7 days. A Numeric Rating Scale for Pain (NRS, 0–100 mm) was used to assess the level of pain. The safety assessment was based on the collection of data on the registration of adverse events, including opioid-associated adverse effects.Results. Enteral and parenteral morphine administration for 7 days demonstrated a statistically significant decrease in the intensity of pain syndrome in cancer patients. The use of morphine hydrochloride in tablets reduced the number of additional analgesics prescribed for cancer patients. Regarding opioid-associated adverse effects, a statistically significant difference in the incidence of constipation between two groups was observed.Conclusion. The study showed that tablets and injectable dosage forms of morphine hydrochloride were comparable in efficacy and safety profile, thus predetermining the widespread clinical use of drugs produced by the domestic manufacturer in accordance with the “pain relief ladder”, proposed by WHO.